2012
DOI: 10.1124/jpet.112.194704
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Purinergic Neuromuscular Transmission by Phorbol Dibutyrate is Independent of Protein Kinase C in Murine Urinary Bladder

Abstract: Parasympathetic control of murine urinary bladder consists of contractile components mediated by both muscarinic and purinergic receptors. Using intracellular recording techniques, the purinergic component of transmission was measured as both evoked excitatory junctional potentials (EJPs) in response to electrical field stimulation and spontaneous events [spontaneous EJPs (sEJPs)]. EJPs, but not sEJPs, were abolished by the application of the Na ϩ channel blocker tetrodotoxin and the Ca 2ϩ channel blocker Cd 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…The authors raised the possibility that EJPs result from the activation of two different membrane conductances and that the variation in EJP amplitude may be related to the degree of coupling between smooth muscle cells in and between muscle bundles. EJPs, but not sEJPs, recorded in mouse bladder, were abolished by tetrodotoxin, but both EJPs and sEJPs were abolished by NF279, a P2X1 receptor antagonist [602]. The authors also showed that phorbol dibutyrate potentiated EJP amplitudes, but not those of sEJPs, probably by increasing ATP release from the nerve varicosities.…”
Section: Parasympathetic Cotransmissionmentioning
confidence: 51%
“…The authors raised the possibility that EJPs result from the activation of two different membrane conductances and that the variation in EJP amplitude may be related to the degree of coupling between smooth muscle cells in and between muscle bundles. EJPs, but not sEJPs, recorded in mouse bladder, were abolished by tetrodotoxin, but both EJPs and sEJPs were abolished by NF279, a P2X1 receptor antagonist [602]. The authors also showed that phorbol dibutyrate potentiated EJP amplitudes, but not those of sEJPs, probably by increasing ATP release from the nerve varicosities.…”
Section: Parasympathetic Cotransmissionmentioning
confidence: 51%
“…In contrast with the human detrusor muscle, neurotransmission to murine detrusor muscle consists of both cholinergic and purinergic components (Searl and Silinsky, 2012a). Indeed, contractions in response to EFS (10 Hz, 5 seconds duration) were reduced to 63% 6 8% of the control after application of atropine (n 5 8), confirming that a substantial portion of the contractile response in the murine bladder is mediated by purinergic receptors.…”
Section: Resultsmentioning
confidence: 56%
“…The purinergic component of neurotransmission in the murine detrusor provides a means to measure both the purinergic component of neurotransmission and changes in postjunctional sensitivity to ATP by exploiting the electrically evoked EJP and spontaneous sEJP amplitudes (Searl and Silinsky, 2012a). As shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations